A Qualitative Evaluation Process for Educational Programs Serving Handicapped Students in Rural Areas - Lucille Annese Zeph (Journal of Research in Rural Education, 1985)
This paper describes a qualitative methodology designed to evaluate special education programs in rural areas serving students w.ithsevere special needs. A rationale is provided for the use of the elements of aesthetic criticism as the basis of methodology, and specific descriptions of the steps for its implementation and validation are provided. Some practical limitations and particular areas of usefulness are also discussed.